PENGARUH GREEN AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK RAMAH LINGKUNGAN (STUDI KASUS PADA KERTAS MULTIFUNGSI SINAR DUNIA DAN BOLA DUNIA) - Ibnu Sina Hi Yusuf (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2017)
The purposeof this study is todetermine the influence of Green Awareness on the Decision of Purchasing of Environmentally Friendly Products (Case Study on Sinar Dunia and Bola Dunia Papers) .As indicated in green awareness is consumer environmental concern, environmentally friendly product, brand image, and price. From the result of multiple linear regression analysis in this study it is known that consumer environmental awareness variable has a negative and significant effect on the decision of purchasing environmentally friendly products, environmentally friendly product variables have positive and significant influence on the decision of purchasing environmentally friendly product, brand image variable have positive and significant influence to purchase decision Environmentally friendly products, and price variables have a positive and significant influence on the decision to purchase environmentally friendly products. This is indicated by the value of R Square of 43.3%, while the remaining 56.7% influenced by other variables not examined in this study.